Sosialisasi Perilaku Hidup Bersih Dan Sehat di Sekolah Dasar Negeri Naku - Ronald Darlly Hukubun; Juan Marchel Paulus; Jembris Nustelu; Vivin Ayuasthika; Yansen Jagatri Kufla; Laury Marcia Chara Huwae; Laura Bianca Sylvia Huwae (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2024)
The aim of this socialization activity is to increase the knowledge of Naku Christian Elementary School students about clean and healthy living behavior (PHBS) and teach clean and healthy living habits both in the school and family environment. The method used is socialization about PHBS. The results obtained after community service activities were carried out were increasing students knowledge about PHBS principles, being able to change students attitudes towards the importance of implementing PHBS principles, being able to apply PHBS in the school environment and in the family. UKS teachers know more about the challenges of teaching PHBS principles to students and how to create a healthy environment at school, including a canteen that meets health requirements and in the next stage students are expected to be able to become examples of PHBS behavior and as agents of change to spread knowledge about PHBS in the family environment and the wider community.